GE_GERICHTE C/18302/2015 vom 22. Januar 2016 - GE Cour de justice (2016)
COMPÉTENCE; CAS CLAIR; VALEUR LITIGIEUSE; CONCLUSIONS; CONCIERGE; EXPULSION DE LOCATAIRE | CPC.317.1; CPC.257; LTPH.1.1.a; LOJ.86; LOJ.89.1.a